Two refractory Wild 2 terminal particles from a carrot‐shaped track characterized combining MIR/FIR/Raman microspectroscopy and FE‐SEM/EDS analyses. (4th March 2014) - Rotundi, A.; Rietmeijer, F. J. M.; Ferrari, M.; Della Corte, V.; Baratta, G. A.; Brunetto, R.; Dartois, E.; Djouadi, Z.; Merouane, S.; Borg, J.; Brucato, J. R.; Le, L.; et al.
Abstract We present the analyses results of two bulk Terminal Particles, C2112, 7, 171, 0, 0 and C2112, 9, 171, 0, 0, derived from the Jupiter‐family comet 81P/Wild 2 returned by the Stardust mission. Each particle embedded in a slab of silica aerogel was pressed in a diamond cell. This preparation, as expected, made it difficult to identify the minerals and organic materials present in these particles. This problem was overcome using a combination of three different analytical techniques, viz. FE‐SEM/EDS, IR, and Raman microspectroscopy that allowed identifying the minerals and small amounts of amorphous carbon present in both particles. TP2 and TP3 were dominated by Ca‐free and low‐Ca, Mg‐rich, Mg, Fe‐olivine. The presence of melilite in both particles is supported by IR microspectroscopy, but is not confirmed by Raman microspectroscopy, possibly because the amounts are too small to be detected. TP2 and TP3 show similar silicate mineral compositions, but Ni‐free and low‐Ni, subsulfur (Fe, Ni)S grains are present in TP2 only. TP2 contains indigenous amorphous carbon hot spots; no indigenous carbon was identified in TP3. These nonchondritic particles probably originated in a differentiated body. This work found an unanticipated carbon contamination following the FE‐SEM/EDS analyses. It is suggested that organic materials in the embedding silica aerogel are irradiated during FE‐SEM/EDS analyses creating a carbon gas that develops a strong fluorescence continuum. The combination of the selected analytical techniques can be used to characterize bulk Wild 2 particles without the need of extraction and removal of the encapsulating aerogel. This approach offers a relatively fast sample preparation procedure, but compressing the samples can cause spurious artifacts, viz. silica contamination. Because of the combination of techniques, we account for these artifacts.